The Measuring Efficiency of Waqf Fund : Evidence in Indonesia - Herindar, Evania; Rusydiana, Aam Slamet (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2021)
This study will try to measure the efficiency of waqf funds in zakat institutions in Indonesia using the non-parametric Data Envelopment Analysis (DEA) method. The objects in this study are eight zakat institutions that manage waqf funds in Indonesia. The data in this study comes from the annual reports of each of these institutions during the period 2013-2020. The input variables in this study include operational costs and HR costs. In comparison, the output variables in this study include the collection and distribution of waqf funds. This study indicates that during 2013-2020, the efficiency of zakat institutions in managing waqf funds has a fluctuating trend. This study will also look at the possibility of improving inefficient programs from input and output variables; in general, the main factor in the efficiency of waqf funds lies in the output variable, namely the acceptance and distribution of waqf funds. In addition, this study provides a reference for other decision-making units (DMUs) in improving efficiency, and the average DMU used as a reference is the one who has good professionalism and innovation. Keyword : Waqf fund, Data envelopment analysis (DEA), Efficiency, Indonesia